2020
DOI: 10.4103/jehp.jehp_754_19
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges of social media for health knowledge management: A narrative review

Abstract: INTRODUCTION: Social media is becoming a new tool for developing health knowledge management. However, despite the rapid growth of research in this area, few attempts have been made to review previous research. This study tried to summarize the opportunities and challenges of using social media to managing health knowledge. METHODOLOGY: This article used a narrative approach to collect and review studies. In this review, published documents during 2010–2019 were retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The findings in this review support the need for codes of conduct, policies and guidelines to be established specifically for the use of social media by healthcare organisation employees (Corniati et al 2019 ; El Daouk et al 2020 ; Ghalavand et al 2020 ; Hamilton et al 2016 ; Holdsworth et al 2013 ; Khan et al 2021 ; Peek et al 2015 ; Peluchette et al 2016 ; Popper-Giveon et al 2019 ; Sweet 2012 ). With social media use in general, society is encouraged to take risks, be impulsive and be social.…”
Section: Findings and Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The findings in this review support the need for codes of conduct, policies and guidelines to be established specifically for the use of social media by healthcare organisation employees (Corniati et al 2019 ; El Daouk et al 2020 ; Ghalavand et al 2020 ; Hamilton et al 2016 ; Holdsworth et al 2013 ; Khan et al 2021 ; Peek et al 2015 ; Peluchette et al 2016 ; Popper-Giveon et al 2019 ; Sweet 2012 ). With social media use in general, society is encouraged to take risks, be impulsive and be social.…”
Section: Findings and Discussionsupporting
confidence: 60%
“…However, social media allows the lines between personal and employee online presence to be blurred easily. The call for healthcare organisations to establish social media codes of conduct started a decade ago (Anderson and Guyton 2013 ; Sweet 2012 ), focusing on using social media safely (Ghalavand et al 2020 ). Healthcare organisations must develop, enforce and update policies to address appropriate and inappropriate conduct on social media, including employee agreements, orientation training, employee handbooks and performance appraisals (Suby 2013 ).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have documented the prevalence of misinformation on health-related issues such as vaccination, pandemic, non-communicable diseases, and medical treatment [ 8 ] and its role in diverting individuals from performing correct health behaviour, including preventive behaviour during the COVID-19 pandemic. Several factors, such as poor information infrastructure, lack of proper knowledge-sharing culture, and resistance to technology adaptation, remain the main challenges in dealing with misinformation [ 9 ]. Previous studies have shown that exposure to misinformation has led people to perform misguided COVID-19 preventive behaviours while discouraging them from performing the recommended ones [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of social networks sites as a new form of digital media and communication channel has brought many challenges for the health system [ 1 3 ]. The widespread use of social media affects the context in which professional behaviours are exhibited and how they are interpreted [ 4 ].…”
Section: Introductionmentioning
confidence: 99%